Reducing urban poverty in the global South - Satterthwaite, David (London Taylor & Francis Group, 2014)
Urban areas in the Global South now house most of the world?s urban population and are projected to house almost all its increase between now and 2030. There is a growing recognition that the scale of urban poverty has been overlooked ? and that it is increasing both in numbers and in the proportion of the world?s poor population that live and work in urban areas.
Includes bibliographical references and index.
Keywords: Urban poor -Developing countries